Development of a nurse home visitation intervention for intimate partner violence - Jack Susan M; Ford-Gilboe Marilyn; Wathen C Nadine; Davidov Danielle M; McNaughton Diane B; Coben Jeffrey H; Olds David L; MacMillan Harriet L (BMC, 2012)
Abstract Background Despite an increase in knowledge about the epidemiology of intimate partner violence (IPV), much less is known about interventions to reduce IPV and its associated impairment. One program that holds promise in preventing IPV and improving outcomes for women exposed to violence is the Nurse-Family Partnership (NFP), an evidence-based nurse home visitation program for socially disadvantaged first-time mothers. The present study developed an intervention model and modification process to address IPV within the context of the NFP. This included determining the extent to which the NFP curriculum addressed the needs of women at risk for IPV or its recurrence, along with client, nurse and broader stakeholder perspectives on how best to help NFP clients cope with abusive relationships. Methods Following a preliminary needs assessment, an exploratory multiple case study was conducted to identify the core components of the proposed IPV intervention. This included qualitative interviews with purposeful samples of NFP clients and community stakeholders, and focus groups with nurse home visitors recruited from four NFP sites. Conventional content analysis and constant comparison guided data coding and synthesis. A process for developing complex interventions was then implemented. Results Based on data from 69 respondents, an IPV intervention was developed that focused on identifying and responding to IPV; assessing a client's level of safety risk associated with IPV; understanding the process of leaving and resolving an abusive relationship and system navigation. A need was identified for the intervention to include both universal elements of healthy relationships and those tailored to a woman's specific level of readiness to promote change within her life. A clinical pathway guides nurses through the intervention, with a set of facilitators and corresponding instructions for each component. Conclusions NFP clients, nurses and stakeholders identified the need for modifications to the existing NFP program; this led to the development of an intervention that includes universal and targeted components to assist NFP nurses in addressing IPV with their clients. Plans for feasibility testing and evaluation of the effectiveness of the IPV intervention embedded within the NFP, and compared to NFP-only, are discussed.